Clinical characteristics of postoperative necrotizing enterocolitis in patients with congenital jejunoileal atresia and its risk factors - Wei Lu; Yuan Cai; Jiexiong Feng; Xiaofeng Xiong; Fuzhong Xing; Jixin Yang; Yuhang Yuan; Xuyong Chen (BMJ Publishing Group, 2024)
Objective To review postoperative necrotizing enterocolitis (NEC) in patients with jejunoileal atresia (JIA) and to explore the potential risk factors related to the concurrence of NEC.Methods Patients diagnosed with JIA who received surgical treatment from January 2016 to June 2021 were enrolled. Demographics, viral infection of the fetus, transfusion within 48 hours before NEC, sepsis before JIA repair, pathological and anatomical classification of JIA, combined malformation, occurrence time of NEC after the operation, treatment, and prognosis of patients were analyzed. Patients were divided into NEC group and non-NEC group, and all patients were followed up for 3-6 months to observe for complications.Results A total of 180 patients with JIA were included, of whom 12 were diagnosed with NEC after surgery and 1 patient with NEC died during follow-up. The average age, birth weight, gestational age, proportion of premature infants, proportion of preoperative infections, and pathological classification of JIA did not significantly differ between the two groups. The probability of patients with proximal jejunal atresia (PJA) in the NEC group (58.3%) was higher than that in the non-NEC group (22.6%) (p=0.011), and patients with PJA had longer parenteral nutrition time than patients without PJA (26.64±9.21 days vs 15.11±6.58 days, p<0.001).Conclusion PJA was more likely to be associated with concurrent NEC after surgery, which is a highly NEC-related risk factor inherent in JIA.